Determinantes de la salud en relación con la mordida abierta - Cueva Jiménez, Dylan Miguel (2024)
Open bite is a condition in which the upper and lower front teeth do not make contact when closing the mouth, leaving a gap between them. This condition, although preventable, affects a large part of the population and is often associated with oral habits such as atypical swallowing, digital suction, and mouth breathing, as well as to a lesser extent with hereditary and congenital disorders. The aim of this research was to conduct a literature review to analyze and understand the factors contributing to the development of open bite and its impact on oral health, in order to develop effective prevention and treatment strategies. The methodology used in this study was cross-sectional, descriptive, analytical, and documentary, with a retrospective approach to different digital sources and scientific articles related to the topic. 46 sources were found, of which 14 were excluded for being irrelevant. Databases such as Dialnet, Scielo, Scopus, Web of Science, and Mediagraphic were consulted. The results showed that digital suction habits and lingual interposition are the main factors contributing to the formation of open bite. It was also found that behavioral determinants have a greater influence on the development of this condition. In conclusion, it can be stated that poor oral habits, especially digital suction, are the main etiological factors causing malocclusions such as anterior open bite in children aged 4 to 10 years. It was also observed that behavioral habits, such as thumb sucking, have a greater influence on the development of open bite compared to social factors, such as access to dental care and socio-economic and cultural factors